MEMPERSOALKAN OBJEKTIVITAS HUKUM: SUATU PERBINCANGAN FILSAFAT HUKUM - Aditya Yuli Sulistyawan (Faculty of Law, Universitas Diponegoro, 2012)
The dominance of legal positivism in studying and law enforcement is a reality. Scientism present law jurisprudence conceived as something that exists in visibility, following its straightforward, rational, and objective. The presence of a real law asks organized law objectively. Objectivity is done by freeing the mind subject to legal reality that already exists into objects. It means that the object will have to put forward. Law is something desired by written texts [object itselQ, because that's the truth of reality believed. However, the issue is whether it is possible objectivity held in the positivistic law enforcement? The answer on this question will be available when we explain in the Philosophy of Law.